IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM BY APPLYING THE PROJECT BASED LEARNING (PJBL) MODEL IN LEARNING ISLAMIC RELIGIOUS EDUCATION - Istiqomah, Shofia; Aisyah, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Project Based Learning is a learning approach that gives students the freedom to plan learning activities, carry out projects collaboratively, and produce work products that can be presented to others. This research explains the implementation of the independent curriculum by applying the basic learning project model for learning Islamic religious education. This research can be seen in terms of type and nature, so it takes the form of a descriptive qualitative approach. The results of this research are the research method used in this research, namely literature review. The project-based learning model is one of the appropriate models for using the independent curriculum, because this learning model can develop the potential of students in increasing their creativity in accordance with the Pancasila student profile which is one of the characteristics of the independent curriculum. In this project-based learning, it is in accordance with Islamic religious education learning by utilizing used goods and making wall magazines that are related to Islamic Religius Education material such as zakat, hajj, and others related to Islamic Religius Education material.